2021
DOI: 10.1161/atvbaha.120.315525
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA Calm4 Regulates Hypoxia-Induced Pulmonary Arterial Smooth Muscle Cells Pyroptosis via the Circ-Calm4/miR-124-3p/PDCD6 Axis

Abstract: Objective: Circular RNAs are emerging as important regulators of pulmonary hypertension where pyroptosis plays a critical role. However, whether and how the circular RNAs regulate pyroptosis remained unexplored. Here, we show evidence for the involvement of a specific circular RNA known as circ-Calm4 in pulmonary hypertension and the underlying signaling pathway in pyroptosis. Approach and Results: Circ-Calm4 was upregulated in both mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 52 publications
(62 reference statements)
0
48
0
Order By: Relevance
“…Although some reports have proved the role of circRNA in cardiovascular disorders and pulmonary hypertension, few studies focused on circRNA in COPD-associated pulmonary vascular remodeling (Yang et al 2020;Jiang et al 2021). In this study, we used microarray analysis to identify changes in the expression pro les of circRNAs in lung tissues of COPD patients and in PASMCs exposed to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Although some reports have proved the role of circRNA in cardiovascular disorders and pulmonary hypertension, few studies focused on circRNA in COPD-associated pulmonary vascular remodeling (Yang et al 2020;Jiang et al 2021). In this study, we used microarray analysis to identify changes in the expression pro les of circRNAs in lung tissues of COPD patients and in PASMCs exposed to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“… 71 Their subsequent study indicated that circ_Calm4 also acted as a ceRNA, regulating the expression of miR‐124‐3p/ PDCD6 to modulate the pyroptosis of hypoxia‐cultured PASMCs (Figure 3). 69 Moreover, Yang et al reported that mmu_circ_0000790 competitively bound to miR‐374c, thus upregulating FOXC1 expression and activating notch pathway in the pulmonary vascular tissues of HPH mice and hypoxia‐cultured PASMCs (Figure 3). 77 Guo et al reported that circATP2B4/miR‐223/ ATR axis regulated the proliferation, migration, and apoptosis of PASMCs induced by hypoxia 24 .…”
Section: The Functions Of Circrnas In Phmentioning
confidence: 99%
“…Using RNA seq, it has been demonstrated that circRNA levels generally increase or decrease in different types of PH. 69,70 Although the limited number of PH-related circRNAs studies to date have only focused on their functions as biomarkers and miRNA sponges, the data clearly indicate that circRNAs had a critical effect on the pathogenesis of PH, which are summarized in Figure 3. 46,71…”
Section: The Fun C Ti On S Of Circrna S In Phmentioning
confidence: 99%
“…In the exploration of diabetic cardiomyopathy (DCM), Yang et al emphasized that hsa_circ_0076631, named caspase-1-associated circRNA (CACR), was significantly increased in the serum of diabetic patients, and the silencing of CACR could reduce caspase-1 expression by sponging miR-214-3p, thereby restraining inflammation and pyroptosis of cardiomyocytes ( Yang F. et al, 2019 ). Jiang et al proved that in hypoxia-induced pulmonary arterial smooth muscle cells (PASMCs), circ-Calm4 increased the expression of programmed cell death protein 6 (PDCD6) through sponging miR-124-3p, and ultimately triggered pyroptosis ( Jiang et al, 2021 ). Although the current research on circRNA-related ceRNA in pyroptosis is insufficient, it is believed that the achievements in this field would be even greater in over time.…”
Section: Cerna Cross-talk In Pyroptosismentioning
confidence: 99%